Da'wah In the Ginseng Country: The Strategy of PCINU and the Ammar Bin Yaser Mosque in Maintaining the Religious Commitment of Indonesian Citizens in South Korea - Auliya Azzahra Mursidi; Muhammad Saifuddin; Khairullah Khairullah (Interdisciplinary Social Studies, 2025)
This research aims to identify and analyze the communication strategies of the Special Branch Management of Nahdlatul Ulama in South Korea in maintaining the religious commitment of the Indonesian Muslim community at the Ammar Bin Yaser Mosque in South Korea. In this rapidly advancing era of globalization, traveling abroad for various reasons such as study, work, or marrying foreign nationals has become commonplace. One country that attracts significant attention from Indonesian citizens is South Korea. Living in a country with different cultural and social systems, the Indonesian Muslim community in South Korea faces several major challenges in maintaining their religious commitment. The strategies implemented by the Ammar Bin Yaser Mosque and the Special Branch Management of Nahdlatul Ulama (PCINU) in maintaining the religious commitment of Indonesian Muslim citizens in a minority country should serve as a reference for preachers. Using a qualitative method, the researcher found that the approaches used are social, cultural, and psychological. These three approaches are implemented through regular religious study sessions, spiritual training programs, the strengthening of community solidarity, and the use of social media to expand the reach of da’wah.